1995
DOI: 10.1021/jm00016a004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vitro and in Vivo Antitumor Activity of a Series of Trans Platinum Antitumor Complexes

Abstract: The synthesis of a series of platinum complexes of trans coordination geometry [centered around the general formula, trans-ammine(amine)dichlorodihydroxoplatinum(IV) plus corresponding tetrachloroplatinum(IV) or Pt(II) counterparts] is described as part of a drug discovery program to identify more effective platinum-based anticancer drugs, particularly targeted toward the circumvention of resistance to cisplatin. Complexes have been evaluated for antitumor activity using in vitro and in vivo tumor models. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 18 publications
(31 reference statements)
4
52
0
Order By: Relevance
“…Interestingly, however, compound 1 did not show any statistically significant effect in CH1 tumor progression relative to control mice. These results indicate that compound 2 shows a promising level of in vivo antitumor activity against a human tumor xenograft in comparison to both the Pt(II) counterpart (compound 1) and transplatin (Kelland et al, 1995).…”
Section: Downloaded Frommentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, however, compound 1 did not show any statistically significant effect in CH1 tumor progression relative to control mice. These results indicate that compound 2 shows a promising level of in vivo antitumor activity against a human tumor xenograft in comparison to both the Pt(II) counterpart (compound 1) and transplatin (Kelland et al, 1995).…”
Section: Downloaded Frommentioning
confidence: 79%
“…The resistant cell lines show acquired resistance to cisplatin and were selected with regard to the three major mechanisms of resistance to the drug. In addition, these cell lines have been used previously to identify novel platinum complexes capable of circumventing cisplatin resistance (Kelland et al, 1992(Kelland et al, , 1994(Kelland et al, , 1995. Because cellular and molecular pharmacology studies are essential to understand the relationships between structure and anticancer properties, we have compared the cellular accumulation, DNA binding, interstrand cross-linking efficiency, apoptosis induction, and binding to serum albumin and plasma proteins of the transPt(IV) complex (compound 2) with that of its corresponding trans-Pt(II) analog (compound 1).…”
Section: The Use Of Cis-diamminedichloroplatinum(ii) Known As Cisplamentioning
confidence: 99%
“…The exact level of cisplatin resistance in patients is difficult to define, but at least a twofold resistance is inferred from clinical studies, primarily since responses have been observed when the standard clinical dose of cisplatin is doubled in drug-intensive therapy protocols (Ozols et al, 1984Schilder and Ozols, 1992). In general, resistance to cisplatin may be substantially greater, as judged from studies with tumor cell lines established from clinically refractory tumors, which require cytotoxic concentrations as much as 50-100-fold in excess of those needed for sensitive tumor cells (Hills et al, 1989;Kelland et al, 1995;Hagopian et al, 1999). Thus, the problem posed by cisplatin resistance appears to be more severe than has been acknowledged in the past.…”
Section: Mechanism Of Resistancementioning
confidence: 99%
“…The synthesis of the asymmetric trans-platinum(II) complexes was accomplished through treatment of the symmetric tetra-amine complex with concentrated hydrochloric acid as illustrated in Scheme 1, based on literature procedures [23]. The complexes where fully characterized using 1 H, 195 Pt NMR (Table 1), IR, X-ray diffraction and elemental analysis.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%